Over-current protection circuit design for DC-DC converter in space applications - Long, Jiru (2014)
Presently a major concern about electronic devices operating in space environment is the radiation effects induced by high energetic particles ionizing inside the devices. In order to eliminate these effects, there are two approaches, namely radiation hardened by process and radiation hardened by design. This Final Year Project proposed an efficient and robust design of over-current protection scheme, with high immunity against many radiation effects, such as Single Event Latchup, Single Event Upset and Total Ionizing Dose. The major function of the circuit is to protect power supply and load ICs against Single Event Latchup. A constant transconductance self-biasing circuit is designed to mitigate Total Ionizing Dose effect. A robust radiation hardened voltage reference is designed with a high PSRR of 110 dB and a temperature coefficient of 9.9ppm/°C in the temperature range from -40°C to 125°C. A triple modular redundancy technique is implemented in digital circuitry to enhance the immunity against Single Event Upset. The proposed design is verified using 0.18μm CMOS process. On the basis of Cadence simulation, the circuit is capable of accurately sensing load current and protecting the load when latchup occurs by setting a power cycle of 5ms enough for the load recovering from latchup state. The idea of this over-current protection circuit is verified by testing the hardware prototype. In summary, this proposed design can meet all the objectives of the project and provide the insight and guidance of radiation hardened by design.